Case report: Complex paraneoplastic syndromes in thymoma with nephrotic syndrome, cutaneous amyloidosis, myasthenia gravis, and Morvan’s syndrome - Liu, Huiqin; Dong, Zeqin; Zhang, Milan; Pang, Rui; Xu, Jiajia; He, Pan; Mei, Wenli; Zhang, Shuai; You, Guanqiao; Li, Wei (Frontiers in Oncology, 2022)
Background Apart from myasthenia gravis (MG), thymoma is associated with a wide spectrum of autoimmune paraneoplastic syndromes (PNSs). Here, we report on a rare case presenting with four different PNSs, namely, MG, membranous nephropathy, cutaneous amyloidosis, and Morvan’s syndrome associated with thymoma. Case presentation A middle-aged man was frequently hospitalized because of nephrotic syndrome (stage I membranous nephropathy), cutaneous amyloidosis, and MG with acetylcholine receptor (AChR) antibody and titin antibody positivity. Chest CT showed a thymic mass in the left anterior mediastinum, and he received intravenous immunoglobulin (IVIG), methylprednisolone pulse therapy, thoracoscopic thymoma resection, and radiotherapy. Postoperative pathological examination revealed a type B2 thymoma. During the perioperative stage, his electrocardiogram (ECG) showed myocardial infarction-like ECG changes; however, his levels of cardiac enzymes and troponin were normal, and he had no symptoms of precardiac discomfort. Six months after thymectomy, his nephrotic syndrome and MG symptoms were relieved; however, he presented with typical manifestations of Morvan’s syndrome, including neuromyotonia, severe insomnia, abnormal ECG activity, and antibodies against leucine-rich glioma-inactivated 1 (LGI1) and γ-amino-butyric acid-B receptor (GABABR). His symptoms did not improve after repeated IVIG and steroid therapies. Finally, he received low-dose rituximab, and his symptoms gradually resolved. Conclusion This case serves to remind us that apart from MG, thymoma is also associated with other autoimmune PNSs such as membranous nephropathy, cutaneous amyloidosis, and Morvan’s syndrome. Autoimmune PNSs can present concurrently with or after surgical or medical therapy for thymoma. For Morvan’s syndrome post-thymectomy with LGI1 antibody positivity, B-cell depletion therapy such as intravenous rituximab is an effective treatment.